PERBANDINGAN MOCAF DENGAN TEPUNG KACANG MERAH DALAM PEMBUATAN BROWNIES KUKUS GLUTEN FREE CASEIN FREE (GFCF) - Massytah, Hildha Ayu; Ekawati, I Gusti Ayu; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i01.p01, 2019)
The purpose of this study is to know the effect of ratio between mocaf and red bean flour on the characteristics of steamed brownies Gluten Free Casein Free (GFCF) and to know the right ratio between mocaf and red bean flour to produce the best characteristic GFCF brownies. This study used a Randomized Block Design with one treatment factor. The ratio of mocaf and red bean flour (100%: 0%, 90%:10%, 80%:20%, 70%:30%, 60%:40% and 50%: 50%). The treatment was repeated three times to produce 18 experimental units. Data were analyzed by analysis of variance and continued by Duncan test. The results showed that treatment with 60% mocaf and 40% red bean flour produced gluten free casein free steamed brownies with water content of 26.60%, ash content of 2.45%, protein content of 5.82%, fat content 22.88%, carbohydrate content 42.23%, crude fiber content of 8.11% with rather liked of color, rather liked of texture, liked taste, rather liked of aroma and liked overall reception.